2016
DOI: 10.1016/j.molonc.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal proteins as prognostic biomarkers in non‐small cell lung cancer

Abstract: BackgroundUse of exosomes as biomarkers in non‐small cell lung cancer (NSCLC) is an intriguing approach in the liquid‐biopsy era. Exosomes are nano‐sized vesicles with membrane‐bound proteins that reflect their originating cell. Prognostic biomarkers are needed to improve patient selection for optimal treatment. We here evaluate exosomes by protein phenotyping as a prognostic biomarker in NSCLC.MethodsExosomes from plasma of 276 NSCLC patients were phenotyped using the Extracellular Vesicle Array; 49 antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(153 citation statements)
references
References 31 publications
1
149
0
3
Order By: Relevance
“…Li, Zhang, Zheng, Liu, & Chen, 2017; Pietrowska et al, 2017; Pocsfalvi et al, 2016; Sandfeld-Paulsen, Aggerholm-Pedersen, et al, 2016; Sandfeld-Paulsen, Jakobsen, et al, 2016; Sinha et al, 2018; Tanase et al, 2017; Taylor, Zacharias, & Gercel-Taylor, 2011; van Niel et al, 2018; Weidle et al, 2017)) (Fig. 1).…”
Section: Why Ceramide In Exosomes? It’s All In the Numbersmentioning
confidence: 98%
“…Li, Zhang, Zheng, Liu, & Chen, 2017; Pietrowska et al, 2017; Pocsfalvi et al, 2016; Sandfeld-Paulsen, Aggerholm-Pedersen, et al, 2016; Sandfeld-Paulsen, Jakobsen, et al, 2016; Sinha et al, 2018; Tanase et al, 2017; Taylor, Zacharias, & Gercel-Taylor, 2011; van Niel et al, 2018; Weidle et al, 2017)) (Fig. 1).…”
Section: Why Ceramide In Exosomes? It’s All In the Numbersmentioning
confidence: 98%
“…However, several of the discovered biomarkers either did not quite reflect the clinical disease, or required highly invasive procedures to obtain, and therefore could not be included in routine clinical practice . Additionally, restricted availability of tissue for screening of biomarkers, or those requiring highly invasive procedures for procuring the tissue samples, as found in lung cancer, limits the success of tissue‐based biomarker discovery in cancer . This calls for the need of more accurate and minimally invasive biomarkers for cancer treatment, which makes the biomarkers from liquid biopsies the most coveted in the field .…”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, restricted availability of tissue for screening of biomarkers, or those requiring highly invasive procedures for procuring the tissue samples, as found in lung cancer, limits the success of tissue-based biomarker discovery in cancer. 3,4 This calls for the need of more accurate and minimally invasive biomarkers for cancer treatment, which makes the biomarkers from liquid biopsies the most coveted in the field. 5 Blood or urine-based biomarkers are capable of being collected using minimally invasive procedures, and can be sampled all through the disease course or before and after specific treatments, to monitor disease progression.…”
mentioning
confidence: 99%
“…Profiling the whole proteome of exosomes by mass spectroscopy has revealed various biomarkers in prostate cancer and bladder cancer. A study involving 276 patients with NSCLC identified NY-ESO-1, EGFR, PLAP, EpCAM, and Alix as protein biomarkers for overall survival (Sandfeld-Paulsen, Aggerholm-Pedersen, et al, 2016). Exosomes derived from blood plasma were successfully used for evaluation of multimarker models using the Extracellular Vesicle Array (EV Array) system consisting of 37 antibodies targeting lung cancer-related proteins.…”
Section: Theranostics Applications Of Exosomes In Lung Cancermentioning
confidence: 99%